Plant Growth Variation At Combined Progeny And Provenance Of 5-Year-Old Intsia Bijuga (Colebr. )O.Kuntze In Sobang, Banten - Hamdan , Hamdan Adma; Sugeng , Sugeng Pudjiono; Ismail, Burhan Ismail; Mahfudz, Mahfudz (Jurnal Wasian, 2014)
This study was conducted to evaluate plant growth of Intsia bijuga at 5 years old in Sobang, Banten for supplyinggood genetic material in the future. Establishment of the trial was conducted in 2007 using Randomized CompleteBlock Design (RCBD) that consisted of 6 blocks, 100 families nested in 10 provenances, 4 treeplot for each family witha spacing of 4 x4 m. Measurements were taken periodically every year on the survival percentage, total height andstem diameter at the breast height or dbh. At the age of 5 years showed that the significant differences amongprovenance in survival percentage that ranged from 41.61 to 65.11 %, average of plant height were 1.04 to 2.82 mand dbh 1.24 to 1.59 cm. The growth variation families also showed significant differences in height and diameter. Thesurvival rate ranged from 12.5-91.67 %, average plant height were 0.52-2.55 m and dbh 0.90-2.44 cm. Individual treeheritability estimate for height was height (0.344) while that of diameter was moderate (0.259). Family heritabilitiesfor height and diameter was considered moderate, namely 0.573 and 0.491 respectively. Genetic correlation betweenheight and diameter growth was positive and high (0.834).